MOTIVATIONAL STRATEGIES OF ATTRACTING STUDENTS IN PRACTICING PHYSICAL ACTIVITIES - Mihaela, Ganciu; Oana Maria, Ganciu (European Scientific Journal, ESJ, 2014)
Specialists consider that motivation is rightfully „the essential feature of human behaviour being an dynamical element of the activity ( Maslow, 2007). The purpose of our study is is to know the structures of the motivational characteristics of students enrolled in a physical education course. Understanding the motivational profile of our students will lead to a clear coordination and efficient organization of the physical education at the University of Bucharest. To understand the motivational structure of our students we used the a survey method based on the questionaire. Some motivational strategies to attract students in the practice of physical education include: the diversity of the educational offer and increasing the attractiveness of education activities. The way in which educational objectives are set by the teacher is another motivational strategy for attracting students in practicing at physical activities. Another motivational strategy has in view the importance of feedback and how we need to reward students behaviour/progress. The courses about lifesyle and healthy food is also a strong motivational strategy. In this way students can complete their knowledge about physical activities. Another proposal regarding motivational strategies is reffering to the use of competitions during the classes. Another way to stimulate motivation to sports and general motivation is the teacher’s teaching qualities. Data from our study were compared with results of other studies that have been conducted on similar themes and concluded that the needs of classes of reasons that influence the participation of students at physical activities during college years fall within the specialized literature data.